2020
DOI: 10.4103/jrms.jrms_708_19
|View full text |Cite
|
Sign up to set email alerts
|

Worldwide trends in breast cancer incidence from 1993 to 2012: Age-period-cohort analysis and joinpoint regression

Abstract: Background: Breast cancer is the most common cancer accounting for about one-fourth of total cancer cases and 15% of all cancer deaths among women worldwide. It is important to determine its trend across the regions in the world to find the high-focus regions. Hence, the current study was done to assess the global trends and deviations in the incidence of breast cancer. Materials and Methods: A descriptive trend analysis was done using the data on breast cancer incidenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 22 publications
(11 reference statements)
2
8
0
Order By: Relevance
“…Further investigation is necessary to determine the reasons for the elevated risk in this particular age group. Period effect: Our study identified increasing period effects in female breast cancer incidence and mortality rates from 2003 to 2017, aligning with findings from previous research (8)(9)(10). This observation suggests that socioeconomic transformations and modernized lifestyle changes may constitute the primary factors contributing to the rise in breast cancer incidence and mortality in China.…”
Section: Discussionsupporting
confidence: 90%
“…Further investigation is necessary to determine the reasons for the elevated risk in this particular age group. Period effect: Our study identified increasing period effects in female breast cancer incidence and mortality rates from 2003 to 2017, aligning with findings from previous research (8)(9)(10). This observation suggests that socioeconomic transformations and modernized lifestyle changes may constitute the primary factors contributing to the rise in breast cancer incidence and mortality in China.…”
Section: Discussionsupporting
confidence: 90%
“…15 Krishnamoorthy et al showed increasing worldwide trends in breast cancer incidence during 1993-2012. 16 Also, an overall increasing trend in the incidence of breast cancer was shown in Zurich, Switzerland between 1981 and 2017. 17 A trend analysis of the global incidence of breast cancer showed a rapidly rising incidence in a large number of countries including Asian countries, especially those with rapid economic development in the past several decades.…”
Section: Discussionmentioning
confidence: 98%
“…Where, M for the incidence/DALYs rate of the corresponding age group, μ for the intercept item, α, β, and γ for the age, period and cohort effect, and ε for random error. To address the problem of identification of the model parameters (perfect collinearity of the age, period, and cohort variables), weighted least squares regression was used to partition the effects of age, period, and cohort effect ( 12 , 16 ).…”
Section: Methodsmentioning
confidence: 99%